Karakteristik Minuman Kunyit Asam Instan Terfortifikasi Bubur Rumput Laut (Gracilaria Sp.) - Cahyaning Rini Utami; Risalatul Muawanah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Tamarind turmeric drink is a typical Indonesian herbal or herbal drink, which is popular because of its high antioxidant content. The Foam Mat Drying method is a method that consists of adding foaming and stabilizer ingredients to the liquid and shaking until foam is produced. Addition of seaweed (Gracilaria sp.) to increase the functional value of instant sour turmeric drinks. This research aims to determine the effect of fortification of Gracilaria sp. seaweed porridge in turmeric tamarind drinks on physicochemical characteristics (color, water content, ash content and antioxidants) and organoleptic (color, taste, aroma). This research used a non-factorial Completely Randomized Design (CRD) consisting of only one factor. The factor is the addition of seaweed slurry concentration (0%, 25%, 30%, 35%, and 40%). The best research results in this study were in the P2 treatment (addition of seaweed slurry (Gracilaria sp.) with a concentration of 30%. Following are the results; antioxidant activity: 13.27%, water content: 6.69%, ash content: 4.07% , total dissolved solids: 5.93 ºBrix, color: 3.65 (like), aroma: 2.62 (fair), taste: 3.30 (fair).